Application of the Problem Based Learning Model Combined with Think Pair Share to Improve Conceptual Understanding and Applied Physics Learning Outcomes for Electrical Engineering Students - Setiawan, Doni; Faoziyah, Nina; Dalimarta, Fahmy Ferdian; Kusaeri, Didi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research aims to improve understanding of physics concepts and learning outcomes of Electrical Engineering students at the Politeknik Muhammadiyah Tegal by using the Problem Based Learning model combined with Think Pair Share on dynamic electrical material. The research instruments used were lecturer and student observation sheets, worksheets and test question sheets. In the analysis of students' conceptual understanding, an increase of 8.58% was obtained from cycle I to cycle II. Meanwhile, in the analysis of student learning outcomes in cycle I, the number of students who passed was 61.76%, and in cycle II the number of students who passed was 82.35%. The results of this research show that the application of the Problem Based Learning model combined with Think Pair Share can improve students' understanding of concepts and learning outcomes.